Cysteinyl 1 Receptor Antagonist Montelukast, Does Not Prevent Peritoneal Membrane Damage in Experimental Chronic Peritoneal Dialysis Model in Rats - Sibel Koçak Yucel; Hakki Arikan; Halil Tugtepe; Fulya Cakalagaoglu; Serhan Tuglular; Emel Akoglu; Cetin Ozener (Karger Publishers, 2014)
Background/Aims: Continuous ambulatory peritoneal dialysis (CAPD) induces structural changes in the peritoneal membrane such as fibrosis, vasculopathy and angioneogenesis with a reduction in ultrafiltration capacity. Leukotriene (LT) receptor antagonists have been found to be effective to prevent fibrosis in some nonperitoneal tissues. The aim of this study is to investigate the possible beneficial effect of montelukast, a LT receptor antagonist, on peritoneal membrane exposed to hypertonic peritoneal dialysis in uremic rats. Methods: Of the 48 male, 5/6 nephrectomized Wistar rats 29 remained alive and were included in the study. These studied rats were divided into 3 groups: Group I (n=7) was the control group, Group II (n=8) was treated with 20 ml hypertonic PDF intraperitoneally daily and Group III was treated with montelukast and similar PDF treatment protocol. The morphological and functional changes in the peritoneal membrane as well as cytokine expression were compared between groups. Results: Submesothelial thickness and the severity of the degree of hyaline vasculapathy were more prominent in group III when compared to group I. There were no significant differences between group II and other groups in terms of submesothelial thickness and the severity of the degree of hyaline vasculapathy. Increased expressions of TGF-β and VEGF in parietal peritoneal membrane were found in group II and group III when compared to group I. The amount of TGF-β and VEGF expression were similar in group II and group III. Conclusion: This study suggests that montelukast treatment does not prevent the peritoneal membrane from deleterious effects of hyperosmolar PDF in the uremic environment.